Ugaritic Poetry and Habakkuk 3 - Tsumura, David Toshio 1944- (1989)
The often-suggested connection between Habakkuk 3 and Ugaritic mythology does not seem to be well-founded.
Keywords: ugaritic; habakkuk; Minor Prophets; Prophets; Old Testament